Lights and Shadows of Trait Emotional Intelligence: Its Mediating Role in the Relationship Between Negative Affect and State Anxiety in University Students - Guil, Rocio; Gómez-Molinero, Rocio; Merchán-Clavellino, Ana; Gil-Olarte, Paloma (Frontiers in Psychology, 2021)
Nowadays, students are experiencing difficult and stressful situations due to the Global Pandemic Alert. This changing world can evoke negative emotions that have been traditionally linked to higher anxiety. Researches have been focused on the positive outcomes of trait emotional intelligence (TEI) preventing psychological disorders. However, the possibility that TEI might have a dark side has been neglected. Hence, this study aimed to explore the mediating effect of the three dimensions of TEI in the relationship between negative affect and anxiety symptoms among college students. Participants of this research were 467 undergraduates who completed an online self-reported questionnaire including the Positive and Negative Affect Schedule (PANAS; Watson et al., 1988), the State-Trait Anxiety Inventory (STAI; Spielberger et al., 1970), and Trait Meta-Mood Scale (TMMS-24, Salovey et al., 1995). The global serial mediation model showed that the total amount of variance explained by the global model was 30.8% (R2 = 0.31). Negative affectivity and age accounted for the 15.1% of state anxiety variance (R2 = 0.15; c: B = 0.63, p < 0.001) while 15.7% of the variance of state anxiety was attributed to the direct or indirect effect of the three dimensions of TEI (R2 = 0.16). Five indirect effects presented statistical significance (95% BootCI). The contrast analyses between mediators showed that three indirect effects had higher statistical weigh; the ability of negative affect to increase state anxiety through (i) emotional attention; (ii) emotional clarity, and (iii) serially through emotional clarity and mood repair. Our results indicated that students’ negative emotions lead to higher emotional attention which in turn may enhance state anxiety in two ways: by a direct effect of emotional attention on state anxiety and by a serial effect through emotional clarity. Moreover, when negative affect is associated with lower emotional clarity, anxiety symptoms may also arise. However, when attention and clarity are connected, the negative effect is reversed into a positive one, decreasing state anxiety.